Concept of „long centric" - Martinović Željko; Obradović-Đuričić Kosovka; Teodorović Nevenka S.; Živković Rade (Srpski Arhiv za Celokupno Lekarstvo, 2004)
The objective of this paper was to show the historical perspective of the „long centric" occlusal concept and its importance in the modern dentistry, especially from the gnathological aspect. The „long centric" concept represents therapeutic modality used in modern dentistry and occlusal adjustment in all patients showing differences in strong and weak closure of the lower jaw starting from the position of physiological rest/long centric" concept is applied only for anterior teeth and occlusal movements from rather than toward the center. Whenever the „long centric" parameters are not adequate, occlusal disturbance, resulting from the „wedge" effect during the initial closure of the lower jaw, is present. Different degrees of abrasion or hypermobility of the teeth are often the result of the above-mentioned occlusal disturbances and can potentially trigger bruxism and malfunction. Modus procedendi should be the regular approach of every dentist to any occlusion, because only the built-in „long centric" efficiently contributes to the occlusal stability of the anterior portion of the dentition. All occlusions should be routinely tested regarding their need for „long centric", especially when the extensive therapeutic interventions (conservative, prosthetics) of the occlusal complex are required.